Deskripsi Cemaran Logam (Hg, Cu, Cd) pada Madu Asli, Madu Budidaya dan Madu Merk dengan menggunakan Metode ICP-AES - Wina Fransiska; Wahidin Wahidin (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Honey is derived from plant nectar and pollen collected by bees. Honey contains natural sugars and nutrients but is prone to contamination by heavy metals such as mercury, copper, and cadmium from the environment. Honey quality standards stipulate maximum limits of contamination according to SNI 8664:2018. This study examined copper, mercury, and cadmium levels in native, cultivated, and branded honey using ICP-AES. Samples were randomly collected at the Laboratory of Pharmacy Faculty of University 17 August 1945 and metal levels were determined at the Regional Health Laboratory of DKI Jakarta Province from April-July 2024. Results showed all samples contained copper below the maximum limit of 5.0 mg/kg in the order of 0.243; 0.399; 0.297 mg/kg. Cadmium and mercury in the three honeys were undetected according to SNI's respective maximum limits of 0.2 and 0.03 mg/kg. Therefore, honeys of the three types met quality standards and are safe for consumption.